Apparent nitrogen recovery in milk and early dry season nitrous oxide emission factors for urine deposited by dual-purpose cattle on different soil types - Durango Morales, Sandra Guisela; Barahona Rosales, Rolando; Bolívar Vergara, Diana María; Arango, Jacobo; Verchot, Louis V.; Chirinda, Ngonidzashe (Frontiers Media, 2021)
Pasture conditions influence the nutrients use efficiency and nitrogen (N) losses from deposited excreta. Part of the N is lost as nitrous oxide (N2O), a potent greenhouse gas. The objective of this study was to characterize apparent N recovery in milk of dual-purpose cattle and to quantify N2O emissions from the urine they deposit following grazing on Megathyrsus maximus cv. Mombasa. The N content in the grass and the milk produced by the cattle and the milk urea N (MUN) content were quantified in two contrasting regions of Colombia (Casanare and Atlántico). Dry matter intake (DMI) by the cattle was estimated using the Cornell Net Carbohydrate and Protein System. We used a closed static chamber technique to measure N2O emissions from soils in areas with and without urine patches (21 days in Atlántico and 35 Days in Casanare). Estimated DMI values were 11.5 and 11.6 kg DM day-1, milk production was 6.5 and 5.9 L day-1, apparent N recovery in milk was 24 and 23%, and the MUN content was 4.4 and 17.2 mg N dl-1 in Casanare and Atlántico, respectively. N applied to soil in the form of urine corresponded at rates of 20 and 64 g N m-2 and net cumulative N2O emissions were 350 and 20 mg N2O-N m-2 in Casanare and Atlántico, respectively. Despite low digestibility of offered diet, N recovery in milk was above the values reported at dairy cattle in tropical conditions. High urine-N inputs at Atlántico site did not result in high N2O emissions suggesting that the default Tier 1 emission factor (EF) which is based on N inputs would have overestimated urine-based N2O emissions in Atlántico. Comparing previous studies conducted in Colombia, we observed inter-regional differences by urine-based N2O emissions. This observation suggests that to increase certainty in estimating urine-based N2O emissions, Colombia needs to move towards more region-specific Tier 2 EF and reduce its dependence on the default IPCC Tier 1 EF. In addition, the adoption of Tier 2 EF in the cattle sector will facilitate accounting for the effect of animal diets on N2O inventories.